FOOTPRINTS : IN SEARCH OF FUTURE FOSSILS - Farrier, David (London : 4th Estate, an imprint of HarperCollins Publishers, 2020)
The author surveys the traces we will leave for peoples in the very distant future. He shows that modern civilization has created objects and landscapes with the potential to endure through deep time, including the plastic polluting the oceans, the nuclear waste entombed within the earth, and the thirty million miles of paved roads spanning the planet. This is his meditation on climate change and the Anthropocene, and an urgent search for fossils--industrial, chemical, geological--that humans are leaving behind. -- adapted from inside front dust jacket
Keywords: Human ecology; Fossils; Geology, Stratigraphic -- Anthropocene; Human geography; Nature -- Effect of human beings on; Climatic changes -- Effect of human beings on